The Anti-Ageing Plan - Bentley, Vicci (London Carlton Books, 1997)
This is a practical overview on all aspects of improving and maintaining your appearance. The aim is to help women through the anti ageing maze by casting a critical eye in creams and ther claims, debunking health and nutritional myths, taking a realistic look at cosmetic surgery options and sorting the good from the bad.
Include Color Illustration, Acknowledgment and Index
Keywords: Aging--Prevention -- Beauty, Personal -- Cosmetics